2023
DOI: 10.1186/s12885-023-11073-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sarcopenia on the outcome of patients with left-sided colon and rectal cancer after curative surgery

Abstract: Background The impact of sarcopenia on the outcome of patients with left-sided colon and rectal cancer has not been exhaustively investigated. Thus, the present study was performed to evaluate the effect of sarcopenia on the outcome of patients with left-sided colon and rectal cancer. Methods Patients with pathologically diagnosed stage I, II and III left-sided colon or rectal cancer who had undergone curative surgery between January 2008 and Decem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Nutritional problems frequently exist in colorectal cancer patients, and this problem, which reaches the level of malnutrition in a significant part of them, adversely affects treatment and survival outcomes [ 1 , 5 , 6 ]. The importance of sarcopenia, one of the critical indicators of malnutrition, in patients undergoing colorectal surgery has attracted the attention of researchers, and in a recently published study evaluating 939 patients who underwent left colon and rectal surgery, 61% were found to have sarcopenia in the preoperative period [ 7 ]. Patients with sarcopenia necessitated more intraoperative transfusions, had lower albumin levels, and had prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional problems frequently exist in colorectal cancer patients, and this problem, which reaches the level of malnutrition in a significant part of them, adversely affects treatment and survival outcomes [ 1 , 5 , 6 ]. The importance of sarcopenia, one of the critical indicators of malnutrition, in patients undergoing colorectal surgery has attracted the attention of researchers, and in a recently published study evaluating 939 patients who underwent left colon and rectal surgery, 61% were found to have sarcopenia in the preoperative period [ 7 ]. Patients with sarcopenia necessitated more intraoperative transfusions, had lower albumin levels, and had prolonged hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sarcopenia was found to have a negative impact on all survival parameters and mortality rates. More importantly, the Cox regression analysis revealed that preoperative sarcopenia was an independent predictive factor for worse OS [ 7 ].…”
Section: Discussionmentioning
confidence: 99%